Determining LoA between Left Ventricular EF estimated from Abarquez Formula and Left Ventricular EF measured by 2D Echo - Timbol, John Carlo B (Asian Journal of Medical Sciences, 2020)
Background: The Abarquez formula (aVR QRS amplitude x 2.264) + (age x 0.645) has been offered to provide an estimate for LVEF measured by 2D Echo. However, studies aiming to establish agreement between the Abarquez formula and LVEF measured by 2D Echo are lacking. Aims and Objectives: The aim of this study was to compare the LVEF estimated from 12-lead ECG using the Abarquez formula with the LVEF measured using the 2DED in the following subpopulations: 18-35 years old, 36-60 years old, >60 years old, male, and female patients. To compare these two measurements, the limits of agreement (LoA) by Altman and Bland was used. Materials and Methods: Adult patients admitted in the VLMC from January to May 2019 with both a 12-lead ECG and a 2D Echo were included in the study. LVEF from 2D Echo and LVEF estimated using the Abarquez formula were recorded. Comparison of the two measurements was performed by Altman and Bland method using LoA at 95% confidence interval. This analysis was done using Analyse-It Software. Comparison of the mean differences between the two measurement methods was also done using STATA. Results: LVEF estimate using the Abarquez formula was found to significantly differ from LVEF measured using 2D Echo. Conclusions: The Abarquez formula cannot be used as a surrogate for LVEF measure by 2D Echo.